Peer to Peer Lending Syari’ah: Wadah Investasi Bisnis Sektor Riil untuk Pengembangan UMKM - Fauzia Ulirrahmi (Al-Hiwalah: Journal of Sharia Economic Law, 2023)
The interest of Indonesian people in investing in real sector businesses, particularly MSMEs, is relatively low due to high risks and business uncertainties. Unfortunately, Sharia Financial Institutions have not played an active role in channeling cooperation-based financing. Instead, they have mostly focused on channeling murabahah financing under the buying and selling scheme. However, Sharia P2P Lending can help develop the real sector and have a positive impact on the national economy by reducing bureaucracy and complicated requirements. Sharia P2P Lending is an investment platform in real sector businesses that benefits business actors and investors. The use of Sharia P2P Lending can encourage the public to invest in the real sector because of the following reasons: (1) it provides a safe investment with higher returns compared to conventional investments, (2) it offers access to invest in the real sector with relatively small capital, (3) it allows investors to choose business actors and monitor their investment performance, (4) it has relatively low transaction costs and is easy to conduct transactions online, and (5) it provides protection through risk management and financing management policies carried out by the company.